2010
DOI: 10.1159/000320192
|View full text |Cite
|
Sign up to set email alerts
|

Founder Mutations in the <i>ATP6V1B1 </i>GeneExplain Most Cypriot Cases of Distal Renal Tubular Acidosis: First Prenatal Diagnosis

Abstract: Aims: To investigate clinically and genetically all the distal renal tubular acidosis (dRTA) cases in Cyprus, to study one more family from Greece and to perform the first dRTA prenatal diagnosis. We also tried to find any association with sensorineural hearing loss (SNHL) onset and particular mutations. Methods: Nine dRTA families from Cyprus and one from Greece were analyzed for mutations in ATP6V1B1 gene by DNA resequencing and PCR-RFLPs. Clinical diagnosis was performed by standard criteria. Prenatal diagn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 26 publications
2
5
0
Order By: Relevance
“…Both patients' families originated from Kosovo and were not consanguineous and shared one mutation, the p.Leu81Pro on exon 3, suggesting that this mutation may be more common in this region. The same mutation was also previously found in a patient from Macedonia (4) and patients from Cyprus (11, 13). The second mutation in case I, p.Glu161Lys on exon 6, was described before as a SNP (4).…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Both patients' families originated from Kosovo and were not consanguineous and shared one mutation, the p.Leu81Pro on exon 3, suggesting that this mutation may be more common in this region. The same mutation was also previously found in a patient from Macedonia (4) and patients from Cyprus (11, 13). The second mutation in case I, p.Glu161Lys on exon 6, was described before as a SNP (4).…”
Section: Discussionsupporting
confidence: 75%
“…Mutations in ATP6V1B1 gene cause dRTA with or without SNHL (Table S3) (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14). The majority of these mutations are missense or nonsense mutations.…”
Section: Discussionmentioning
confidence: 99%
“…No phenotype-genotype correlation in dRTA with SNHL was detected in this cohort, as previously described [10]. On the other hand, this study confirms the association between ATP6V1B1 mutations and dRTA with early onset SNHL since childhood, and ATP6V0A4 mutations with dRTA but normal hearing (at least until young adulthood), as reported in the original disease genetic descriptions [7,8,18,25,26], but conflicts with some other reports [9,11], which described ATP6V0A4 gene mutations to be more frequent than ATP6V1B1 ones.…”
Section: Discussionsupporting
confidence: 72%
“…Indeed, Stover et al demonstrated that young adult patients with ATP6V0A4 mutations could develop mild SNHL in the long term [9]. Further, some dRTA patients without early SNHL were found to present mutations in the ATP6V1B1 gene as well [10,11]. …”
Section: Introductionmentioning
confidence: 99%
“…4 The H + -adenosine triphosphatase (ATPase) in the apical border of the intercalated cell of the distal nephron has a multisubunit structure that plays a role in pumping H + into the tubular lumen.5 To date, 26 ATP6V1B1 mutations have been determined as the cause of the disease. 4,613 These include missense, nonsense, deletion, insertion and splice site changes, all of which are predicted to disrupt the structure or abrogate the production, of the normal B1 subunit protein. This leads to loss of expression of the gene in the distal tubules as well as in cochlea and endolymphatic sac.…”
Section: Discussionmentioning
confidence: 99%